2017
DOI: 10.1002/14651858.cd012546
|View full text |Cite
|
Sign up to set email alerts
|

Total serum bile acids or serum bile acid profile, or both, for the diagnosis of intrahepatic cholestasis of pregnancy

Abstract: Total serum bile acids or serum bile acid profile, or both, for the diagnosis of intrahepatic cholestasis of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…TBA is a class of cholesterol metabolites seen in hepatic catabolism and enterohepatic circulation. It is a byproduct of cholesterol breakdown in the liver, and it is linked to cholesterol absorption and physiological metabolism processes [ 18 ]. Therefore, TBA is another one of ICP's diagnostic indications.…”
Section: Discussionmentioning
confidence: 99%
“…TBA is a class of cholesterol metabolites seen in hepatic catabolism and enterohepatic circulation. It is a byproduct of cholesterol breakdown in the liver, and it is linked to cholesterol absorption and physiological metabolism processes [ 18 ]. Therefore, TBA is another one of ICP's diagnostic indications.…”
Section: Discussionmentioning
confidence: 99%
“…A total serum bile acid level of >10 mmol/L is often used to diagnose ICP, although the data are limited and the diagnostic accuracy has been questioned. 6,7 Increases in the levels of transaminases (eg, alanine aminotransferase and aspartate aminotransferase) can also sometimes be seen in ICP, although elevated transaminase levels are not necessary for the diagnosis. Although the bile acid level can be affected by a postprandial state 8 and fasting bile acid measurements are often performed, the differences between the random and fasting results are small.…”
Section: What Is the Differential Diagnosis Of Pruritus In Pregnancy?mentioning
confidence: 99%
“…9 A systematic review published in 2019 stated that a cut off value of 10umol/L for TBA had an overall sensitivity ranging from 72% to 98% and specificity ranging from 81% to 97%. 21 A retrospective study conducted in China revealed that pregnant females had increased fasting serum bile acid levels even without the presence of symptoms and these asymptomatic pregnant females had similar or a higher risk of still birth than patients with ICP. 22 Demir along with his colleagues while establishing relationship between Serum Bile Acid levels and maternal and fetal outcomes found that mean TBA level in preterm birth group was significantly higher as compared to the term birth group.…”
Section: Discussionmentioning
confidence: 99%